Legal perspective on the right to water, water management and concessions in Mexico - Norberto-Cárdenas, Nohemí; Robles-Cuevas, Hugo Oliver; Olvera-Robles, Diana; Ruiz-Canizales, Raúl; Nettel-Barrera, Alina del Carmen (DIXI, 2024)
The purpose of this work is to study the normative configuration around the issue of sustainable water management in Mexico, a contribution from the legal perspective that attempts to contrast the rights enshrined in a legal system and the institutions that are foreseen for its regularization. The function of the hermeneutic study of the right to water and its institutions makes it possible to identify the economic and social dimension inserted in the water regulations and the legal path that allows the concessions of this natural element. The article identifies that the right to water is enshrined both internationally and locally, and is identified as a fundamental right. It is the Mexican State that subscribes to its importance, since it is an essential part of life and human dignity; the State observes international guidelines and represents the ideal of water regulations, operating through institutions, agencies that attend to plans and programs devised in advance. By way of conclusion, this text studies the normative basis in order to contrast it with the social reality in subsequent studies. In this sense, the legal vision and the study of the law give us an overview of what should be, what is ideal and what is desirable in a rule of law embodied in the norm.